Atmospheric, Water and Acoustic Pollution from Hydrocarbon Activities in the American Continent: A Literature Review - Ordoñez-Obando, M.; Rodas-López, O.; Pazmiño-Uruchima, C.; Cañarte-Ayon, C.; Rivera-González, L.; Escobar-Segovia, K. (My University, 2022)
Hydrocarbon activities over the years have been one of the main sources of environmental pollution, creating short and long-term impacts. This study aims to analyze the scientific production of the American continent through a bibliographic review of scientific articles published from the 1970s to the present, in order to contrast relevant scientific information about the types of pollution, water, atmospheric, and acoustic, published in the most important scientific repositories in the world, such as Scopus and Web of Science. The Prisma methodology was adopted for its development. From the plethora of articles collected, a sample of 3879 scientific articles was extracted, from which 3322 of them were excluded, leaving 557 records with remarkable information such as: country, year of publication, type of contamination, remediation if applicable, the associated oil & gas sector, and publication registration on the indexed website. It was noted that the countries with the highest scientific production are the United States, Canada, Brazil, Mexico, and Argentina. Furthermore, the Web of Science, unlike Scopus, contains more indexed publications related to the types of contamination objects relevant to this study. On the other hand, publications focused on water pollution are the only ones that come up with remediations; the rest release a smaller number of publications on these topics. © 2022 by the authors.